Effect of yoga on mindfulness in school going adolescents: A comparative study - Rajesha Halekote Karisetty; Soniya Tiwari (Wolters Kluwer Medknow Publications, 2019)
Context: We are passing through a period of general unrest. People are unable or incapable to adjust to the different circumstances and conditions of life. They are at the breaking point every moment. Our students are no exception to this phenomenon. Yoga incorporates a system of discipline of integrated development of all the aspects of personality. Yoga helps in various ways to balance the sedentary lifestyle. Aims: To investigate the yoga-based module technique on the mindfulness of adolescents. Settings and Design: The study follows pre-post single group design. Fifty-one adolescents were recruited, with age ranging between 11 and 14 years for yoga intervention. The attendance was 100% during the intervention. Materials and Methods: A total of 51 participants were recruited in the present study, with age ranging between 11 and 14 years. The sample size was calculated with G-Power software by fixing the alpha at 0.05, power at 0.80, and an effect size of 0.99 based on the mean and standard deviation of an earlier study. The calculated sample size was 36, but due to possible dropout, we considered 51 individuals in the study. Statistical Analysis Used: Data were found normally distributed using the Shapiro-Wilk test (P > 0.05). Within-group comparison was performed using the paired sample t-test. This was done using RStudio. Results: The normality test of data was done by the Shapiro-Wilk test, and the p value was found to be 0.26, which was >0.05 level, showing that the data were normally distributed. Therefore, the paired sample t-test was done between pre- and post-data; the outcome of the study reported that there was a significant change from pre- to postdata in mindfulness. The p value was found to be 0.012, which proved the alternative hypothesis: the mean of differences is not equal to zero. The mean of the difference is equal to 2.29, which showed that yoga has its effects on mindfulness. Conclusions: In this study, we compared 60 days of yoga-based intervention. The yoga module included some standing and balancing asanas, pranayama mudra, and short relaxation. The effect of this yoga module could be seen in the result of this study, which revealed that this yoga module improves mindfulness in adolescents.